2012
DOI: 10.1002/hipo.22050
|View full text |Cite
|
Sign up to set email alerts
|

Theta‐related gating cells in hippocampal formation: In vivo and in vitro study

Abstract: In this study we extended our earlier in vitro findings concerning the discovery of a novel type of theta-related cells, which we have termed gating cells. There were two main objectives of our present investigations. The first was to determine the distribution of theta gating cells in the separated CA1 and CA3 generators in three different pharmacological conditions: (i) the presence of a cholinergic agonist-carbachol, (ii) the presence of carbachol and GABA(A) ergic antagonist-bicuculline, (iii) the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…To our knowledge, Bocian et al () were the first to describe that PHa‐recorded neurons could also be classified in relation to local PHa theta oscillations. The authors demonstrated that the PHa neurons recorded from anesthetized rats and deafferented PHa preparations can be successfully classified according to ongoing local theta oscillations with the use of the well‐known theta‐related cells classification by Bland and Colom (; supplemented by Konopacki et al, and Kowalczyk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, Bocian et al () were the first to describe that PHa‐recorded neurons could also be classified in relation to local PHa theta oscillations. The authors demonstrated that the PHa neurons recorded from anesthetized rats and deafferented PHa preparations can be successfully classified according to ongoing local theta oscillations with the use of the well‐known theta‐related cells classification by Bland and Colom (; supplemented by Konopacki et al, and Kowalczyk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…All recorded in vitro and in vivo cell discharges were classified according to the criteria that have been developed previously to classify cells in hippocampal formation (Colom and Bland, ; Bland and Colom, ; Bland and Colom, ), supplemented afterword by Konopacki et al () and Kowalczyk et al (b).…”
Section: Discussionmentioning
confidence: 99%
“…In short, the amplitude of theta field potential is variable, occurring as a function of a number of synchronously firing neurons expressing MPOs. Hence, a smaller amplitude of PHa theta field potential vs HPC theta rhythm (Kowalczyk et al, b; Kowalczyk et al, ) may result from a very low density of these cells in the PHa maintained in in vivo conditions. On the other hand, the increased amount of theta‐on phasic cells in the PHa maintained in vitro (vs in vivo conditions) may be reflected in an increased amplitude of in vitro recorded theta (Kowalczyk et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of HPC rhythmic field potential is determined by the specific activity patterns of a number of cells, termed “theta‐related” cells, and “theta‐gating” cells (Colom and Bland, ; Bland and Colom, ; Bland et al, ; Kowalczyk et al, ). These cells program not only the transition from theta state into large irregular activity (LIA) state, but also theta amplitude and power (Colom et al, ; Smythe et al, ; Kowalczyk et al, ). One type of “theta‐related” cells, labelled “theta‐on” phasic cells, specifically determines the appearance of theta rhythm (Bland and Colom, ).…”
Section: Discussionmentioning
confidence: 99%